2017
DOI: 10.1007/s00221-017-4961-0
|View full text |Cite
|
Sign up to set email alerts
|

Visual salience of the stop-signal affects movement suppression process

Abstract: We investigated how the ability to suppress an impending movement is affected by the visual salience of the stop-signal in a reaching countermanding task. We found that when the stop-signal was easy to detect, stop performance was better than when the stop-signal was difficult to detect. In an exploratory analysis, we also found that the change in salience of the stop-signal can have an effect on the speed of response in trials following the stop-signal. This effect occurred together with strategic slowing dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 64 publications
5
21
0
Order By: Relevance
“…They explained this finding in terms of central vs. peripheral focus of “attentional spot‐light” that facilitated detection of the stop‐signal. Further evidence that the visual salience and discriminability of the stop‐signal indeed modulate stopping performance support our findings (Montanari, Giamundo, Brunamonti, Ferraina, & Pani, ; van den Wildenberg & van der Molen, ). In experiment 3, even when orienting gaze was prohibited, subjects exhibited significant deficit in reporting the infrequent second target in the stream of letters about at the same delay.…”
Section: Discussionsupporting
confidence: 89%
“…They explained this finding in terms of central vs. peripheral focus of “attentional spot‐light” that facilitated detection of the stop‐signal. Further evidence that the visual salience and discriminability of the stop‐signal indeed modulate stopping performance support our findings (Montanari, Giamundo, Brunamonti, Ferraina, & Pani, ; van den Wildenberg & van der Molen, ). In experiment 3, even when orienting gaze was prohibited, subjects exhibited significant deficit in reporting the infrequent second target in the stream of letters about at the same delay.…”
Section: Discussionsupporting
confidence: 89%
“…Here we found that, as in humans recently tested in the same task 39 , less salient stimuli deteriorate inhibitory performance and correspond to longer SSRT. These behavioural data were subtended by neural modulations in PMd, participating to action inhibition, that started later in time and showed a less steeper dynamic for stimuli difficult to be processed.…”
Section: Introductionsupporting
confidence: 87%
“…Another aspect of this study is that, from the behavioural point of view, performance in monkeys is very close to the performance observed in humans 39 suggesting that the same neural processes can be at play. This possibility is of particular importance when considering the application of basic neurophysiological knowledge to help clinical investigations.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This suggests that potential stopping markers could be sensitive to variations in processing stages preceding inhibition, a notion which has been supported by recent computational work 22,23 . In fact, several studies show that sensory, attentional and perceptual processes all play into inhibitory performance in the SST [24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%